Better catch them young, but how? A multilingual approach to dialects in education in North Brabant - Doreleijers, Kristel (Dutch Journal of Applied Linguistics, 2022)
This paper discusses the state of affairs of dialect education in the southern Dutch province of North Brabant. The dialects spoken here lack formal recognition. Therefore, the province pursues a heritage policy that protects and promotes the dialects as cultural capital. However, a recent questionnaire among teachers and material developers has revealed that local and provincial initiatives for dialect education have not yet been implemented in a sustainable way in primary and secondary education (Doreleijers, 2021). Although teachers indicate willingness to implement dialect in education, there is a lack of knowledge of existing materials and a discrepancy between demand and the quality of supply. The aim of this paper is to look for ways to implement non-recognized dialects in the curriculum. It argues that the current situation in North Brabant can be improved by integrating dialects into the holistic model for multilingualism in education (Duarte & Günther-van der Meij, 2018).